Correspondence/Letter In Classıcal Turkısh Poetry - Boz, Hülya (Bahir SELÇUK, 2024)
The letter, one of the oldest means of communication and correspondence, is a written message typically conveyed by an intermediary or postal service to inform the recipient. Its history can be traced back to antiquity, and over time, the letter has evolved in terms of its form, method, content, style, and various other characteristics and applications. Although letters have predominantly been written between individuals who are personally acquainted for private purposes, they have also been penned for official, religious, and literary reasons. In classical Turkish literature, there are both prose letters and poetic letters composed in various verse forms. At times, letters have been utilized as an image in couplets to convey the thoughts in one’s mind. This study focuses not on letters as a genre or those written to individuals or institutions, whether private or official, but rather on how poets have employed the concept of the letter as an image and metaphor within their couplets. In this context, the research involved examining divans selected from each century, with a particular focus on ghazals, aiming to identify how poets have approached and developed the concept of the letter in their poetry.

Mektup, kişinin karşı tarafa bir şey bildirmek amacı ile yazıp genellikle bir aracı/postacı tarafından alıcısına ulaştırdığı en eski iletişim ve haberleşme araçlarından biridir. Tarihi İlk Çağ'a kadar götürülebilen mektubun zaman içerisinde kullanım şekil ve yöntemi ile içerik, üslûp gibi birçok özelliği ve kullanım alanlarının değişip geliştiği görülmüştür. Çoğunlukla muhatapların birbirini bizzat tanıdığı kişiler arasında özel amaçlarla mektuplar yazılmış olsa da resmî, dinî, edebî sebeplerle de mektuplar kaleme alınmıştır. Klasik Türk edebiyatında mensur mektuplar ve çeşitli nazım şekilleriyle yazılmış manzum mektuplar mevcuttur. Kimi zaman beyitlerde mektuplardan zihindeki tasarıları aktarmaya yardımcı olacak bir imge olarak yararlanıldığı görülmüştür. Bu çalışma, edebiyatımızda bilhassa kişi ya da kurumlara yazılmış özel ya da resmî mektuplar ve bir tür olarak mektup konusundan ziyade şairlerin beyitlerinde mektup konusunu bir imge ve metafor olarak nasıl işlediklerinin tespiti üzerinedir. Bu bağlamda çalışma oluşturulurken her yüzyıldan seçilen divanlar taranarak özellikle gazeller incelenmiş, şairlerin şiirlerini oluştururken mektup kavramını nasıl ele alıp hangi yönlerden işlediklerinin tespiti hedeflenmiştir.
KLASİK TÜRK ŞİİRİNDE MEKTUP/MEKTUPLAŞMA
Keywords: Classical Turkish Literature; Klasik Türk Edebiyatı